A neuropathy‐associated kinesin KIF1A mutation hyper‐stabilizes the motor‐neck interaction during the ATPase cycle. (8th February 2022) - Morikawa, Manatsu; Jerath, Nivedita U; Ogawa, Tadayuki; Morikawa, Momo; Tanaka, Yosuke; Shy, Michael E; Zuchner, Stephan; Hirokawa, Nobutaka
Abstract: The mechanochemical coupling of ATPase hydrolysis and conformational dynamics in kinesin motors facilitates intramolecular interaction cycles between the kinesin motor and neck domains, which are essential for microtubule‐based motility. Here, we characterized a charge‐inverting KIF1A‐E239K mutant that we identified in a family with axonal‐type Charcot‐Marie‐Tooth disease and also in 24 cases in human neuropathies including spastic paraplegia and hereditary sensory and autonomic neuropathy. We show that Glu239 in the β7 strand is a key residue of the motor domain that regulates the motor‐neck interaction. Expression of the KIF1A‐E239K mutation has decreased ability to complement Kif1a +/– neurons, and significantly decreases ATPase activity and microtubule gliding velocity. X‐ray crystallography shows that this mutation causes an excess positive charge on β7, which may electrostatically interact with a negative charge on the neck. Quantitative mass spectrometric analysis supports that the mutation hyper‐stabilizes the motor‐neck interaction at the late ATP hydrolysis stage. Thus, the negative charge of Glu239 dynamically regulates the kinesin motor‐neck interaction, promoting release of the neck from the motor domain upon ATP hydrolysis. Synopsis: KIF1A‐mediated axonal transport is driven by interaction cycles between the kinesin's motor and neck domains. Characterization of a KIF1A mutant identified in a family with Charcot‐Marie‐Tooth disease reveals that dynamic dissociation of the motor‐neck interaction via the β7 domain is essential for neuronal function. A familial charge‐inverting KIF1A‐E239K variant is associated with axonal‐type Charcot‐Marie‐Tooth disease and other cases of human neuropathies. KIF1A‐E239K exhibits impaired ability to complement Kif1a +/– neurons. Mutant KIF1A shows significantly reduced velocity and ATPase activity. Excess positive charge on the β7 strand caused by E239K mutation electrostatically interacts with a negative charge on the neck. E239K mutation hyper‐stabilizes motor‐neck interaction in a late ATP hydrolysis state, leading to a delay in the ATPase cycle. Abstract : A new mutation in KIF1A identified in a family with Charcot‐Marie‐Tooth disease supports that the dissociation phase of the motor‐neck interaction is important for the kinesin motor cycle and axonal cargo transport.